Optical fiber ring resonator as a high-resolution spectrometer: characterization and applications with single line diode lasers - Presti, Damián Arie (2018)
An optical fiber ring resonator (OFRR), a wavelength sensor for testing a single-mode laser system in a wide range of temperature, is presented. We will show that it is possible to calibrate, in relative form, a scale ofwavelength, to determine, accurately enough, a thermally induced laser detuning, using the free spectral range of an OFRR. The optical circuit was constructed using 2 × 2 (50/50) optical fiber coupler obtaining an OFRR of10-cm ring radius. A single-mode diode laser system has been launched into the OFRR, and different experiments have been performed. We tested the OFRR performance, considering fluctuations in the laser wavelengthcaused by small temperature instabilities, measuring the output intensity from the ring resonator. Theoretical simulations and experimental results were in agreement with the expected behavior. Furthermore, OFRR systemscan be used as an excellent control tool to test the wavelength stability for a narrowband laser diode and act as a part of a control system.